2021
DOI: 10.1111/codi.15554
|View full text |Cite
|
Sign up to set email alerts
|

Urinary dysfunction after colorectal cancer treatment and impact on quality of life—a national cross‐sectional study in males

Abstract: Aim Despite advances in the treatment of colorectal cancer, postoperative urogenital dysfunction is still a problem although its exact extent remains unclear. The aim of this study was to identify the prevalence and patterns of urinary dysfunction in men following treatment for colorectal cancer and the impact of urinary dysfunction on quality of life. Method A retrospective national Danish cross‐sectional study was performed in patients treated for colorectal cancer between 2001 and 2014. Patients answered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This improvement is seen not only in the Western world but also in other geographical areas where high-quality care is available [2]. A growing number of CRC survivors suffer from a broad spectrum of late sequelae, including bowel, urinary, sexual dysfunction, fatigue, psychological distress, insomnia, and pain, all of which may severely affect the quality of life (QoL) [3][4][5][6][7][8][9]. Severe persistent postsurgical pain is a…”
mentioning
confidence: 99%
“…This improvement is seen not only in the Western world but also in other geographical areas where high-quality care is available [2]. A growing number of CRC survivors suffer from a broad spectrum of late sequelae, including bowel, urinary, sexual dysfunction, fatigue, psychological distress, insomnia, and pain, all of which may severely affect the quality of life (QoL) [3][4][5][6][7][8][9]. Severe persistent postsurgical pain is a…”
mentioning
confidence: 99%
“…The mechanism of injury leading to urinary dysfunction is thought to be secondary to nerve damage during surgical resection of rectal tumors [53]. Studies have suggested worse urinary function in patients undergoing APR compared to those undergoing LAR; however, when controlled for other risk factors, these were not statistically significant [52,54,55]. The research on the impact of radiation on urinary dysfunction in rectal cancer survivors is mixed [51,54,56].…”
Section: Urinary Dysfunctionmentioning
confidence: 99%
“…Similarly, a large cross‐sectional study on male CRC survivors ( n = 5710; colon n = 3400, rectum n = 2310) found that urinary dysfunction had a significant impact on QoL in 15.8% of RC survivors and 13.6% of CC survivors ( p = 0.017) [132] (2b). Rectal resection seems to be an independent risk factor for developing urinary dysfunction with abdominoperineal excision and/or RT increasing the risk even further [110, 129,131–133] (2b). However, one study reported the urinary symptoms induced by RT to affect men only and to be transient [125] (2b).…”
Section: Scientific Evidencementioning
confidence: 99%
“…However, one study reported the urinary symptoms induced by RT to affect men only and to be transient [125] (2b). Other risk factors include low tumour height (<5 cm from the anal verge), lymph node involvement, preoperative urinary dysfunction and advanced age [125, 131, 132, 134] (2b).…”
Section: Scientific Evidencementioning
confidence: 99%